Polyalthia montis-silam - Tsen, S.,; Colin Ruzelion Maycock; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Polyalthia montis-silam is restricted to Mount Silam area and Madai Hill in Lahad Datu district. The estimated area of occupancy (AOO) and extent of occurrence are 16 km2 and 47 km2, respectively. Due to land-use changes there has been an estimated decline of 20% in AOO. Fire is a potential threat that could drive this species to Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Polyalthia-montis-silam is endemic to Sabah, Malaysia. It was recorded from Lahad Datu district.